Impact of FLD Intervention on Yield, Adoption and Horizontal Spread of Oilseed Crops in Pali District of Rajasthan, India - Singh, Dheeraj; Chaudhary, M.K.; Kumar, C.; Kuri, B.R.; Tetarwal, A.S. (Annals of Arid Zone, 2023)
In arid zone old varieties and poor management practices leads to the failureof oilseed crops facing heavy losses to the farmers. Introduction of better varieties withthe adoption of scientific cultivation can help to solve this problem. To prove this theoryfrontline demonstrations (FLDs) were conducted in Pali district for sesame and mustardcrop during 2017-2020 on farmer’s field according to package of practices recommendedfor this zone, farmers practice also taken as control to evaluate the performance of FLDsin cluster. The results revealed that there was a significant raise in yield of mustardover the control by 47.00% and sesame by 46.00% respectively. Front line demonstrationsrecorded higher mean net return (Rs. 39762.50 ha-1) with higher benefit ratio (2.86) underimproved technologies of mustard as compared to local checks. In sesame also highermean net return (Rs. 18655.73 ha-1) with higher benefit ratio (2.06) under improvedtechnologies was recorded as compared to local checks. Therefore, the stakeholders whoare engaged in transfer of agriculture technologies on farmer’s field should pay moreattention conducting frontline demonstrations (FLDs) extensively in cluster approach forenhancing productivity potential of and to make rapid spread of flagship technologies.